PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN MENGGUNAKAN METODE SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 47 PEKANBARU - Mike Okta Viola; Zariul Antosa; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was motivated by low student learning outcomes of 38 students, only 9 complete with average 57,60 and KKM of school 72. Because the result was too low, the teacher still use lecture method in teaching learning, the teacher doesn’t have much more skill in developing teaching methods, teachers are only guided by manual book, the number of textbooks was inconsistent with the number of students, the students do not ask the teacher about unfamiliar material, the lack of student interaction with the other students, the students are unable to communicate verbally. The purpose of this research was to improved the teaching learning outcomes of students’ social studies of fourth level at elementary school 47 state Pekanbaru by presenting cooperative learning model was used scramble method. This study was a classroom action research, consisted of two cycles. Each cycle consists of two meetings and one daily test. This research was conducted at elementary school 47 state Pekanbaru. The subjects of this study are the fourth graders of elementary school 47 state Pekanbaru with a total number of 38 students, consisting of 19 boys and 19 girls. The result of the research was obtained by the students before the average action is 57.60 was increased to 65.39 with the percentage increase of 15.32% in cycle I. In cycle II it was increased to 77,36 with the percentage increased 34,30%. Activity of the teacher in cycle I meeting I get 62,50% percentage with low category, at second meeting increase with percentage 70,83% enough category. Furthermore, in the second cycle of meeting I, the activity of teachers has increased with the percentage of 87.50% very good category, the second cycle of II meeting increased again with the percentage of 95.83% very good category. Students activity of first cycle I meeting percentage 58,33% less category, second meeting increased to 66,66% with less category. In the second cycle of meeting I, the student activity was increased to 75,00% good category, at second meeting was increased lag to 83,33% with very good category.Keywords: scramble, social studies’ result